Postura e disfunção temporomandibular: avaliação fotogramétrica, baropodométrica e eletromiográfica - Souza, Juliana Alves (2010)
The temporomandibular disorder (TMD) is a prevalent disease, with manifestations and symptoms involving the structures of the cranio-cervical-mandibular complex and damage of stomatognathic functions. The etiology is multifactorial and, among the factors triggering or perpetuating, has been referred to the body posture. However, a consensus does not exist in the literature about the relationship posture and TMD. In the view of these controversies, this study aimed to evaluate the body posture, the distribution of plantar pressure and the electrical activity of masticatory and cervical muscles in individuals with and without TMD. Sixty individuals of both genders were classified by the Instrument Diagnostic Criteria for Research on Temporomandibular Disorders (RDC/TMD) and divided into study group (SG - 30 individuals, mean age 25 ± 4 years) and control group (CG - 30 individuals, mean age 22 ± 2 years). The body posture was evaluated by photogrammetry (software SAPo v 0.68®) in the anterior, lateral left and posterior view, the plantar pressure distribution by baropodometry(software Footwork) and electrical activity of masticatory muscles (masseter and anterior temporal) and neck (sternocleidomastoid and trapezius), bilaterally. These last evaluations accomplished in the situations of rest and maximal intercuspal jaw position. The SG was characterized by presenting TMD of mixed origin (muscular and articular). Significant differences were observed in 33.33% of photogrammetric measurements between individuals with and without TMD. The cervical distance (p= 0,0043), trunk inclination (p= 0,0038) and valgus of the calcaneus (right p= 0,0087, left p= 0,0444) were significantly larger in the SG and CG individuals showed significant anterior displacement of the vertical alignment of the body (p= 0,033) and anterior pelvic tilt (p= 0,0031). In baropodometric evaluation differences between groups were not found. However, the TMD patients were significantly different between rest and maximum intercuspal position (p= 0,0274), with anterior displacement of the center of pressure in the latter tending to normalization of the distribution of plantar pressure. On electromyographic examination only the left temporal muscle was significantly more active at rest, in individuals of SG (p= 0,0147), with no difference in maximum intercuspal between the groups. The electrical activity increased significantly from the rest to the maximal intercuspal jaw position on the cervical muscles in all individuals. It was observed significant correlations between the posture of the upper cervical spine and the electromyographic activity of right and left masseter in the SG (p= 0,0440, p= 0,0430, respectively), during maximal intercuspal position. From the results it is concluded that the relationship between posture and TMD can not be fully clarified. Although individuals with TMD present more misalignment of the overall body posture, no difference in the distribution of plantar pressures and in the electrical activity of most muscles tested between the groups was observed. However, in the maximal intercuspal, the results of baropodometry and the correlations between photogrammetry and electromyography, in individuals with TMD, suggest the functional relationship of stomatognathic and postural systems.